POLITIK IDENTITAS MUSLIM KAMPUNG JAWA TERHADAP PARTAI KEADILAN SEJAHTERA DI KOTA DENPASAR - Mahayadnya Gede, Gedzha Aldino Putra; Noak, Piers Andreas; Novi Puspitasari, Ni Wayan Radita (Jurnal Nawala Politika, 2015)
ABSTRAK Muslim Javanese village is one of the muslim community often called as migrant communities or minority in Denpasar. In the 2014 legislative elections, muslim Javanese village has been successful delivering one of their representative from Partai Keadilan Sejahtera (PKS) as a member of Denpasar legislator. Political phenomena of muslim Javanese village with their identity, raising political identity to be utilize political parties, specifically PKS in Denpasar as a tool of political struggle. The purpose of this study is to determine and describe the political identity of muslim Javanese village to PKS in Denpasar city. The method for this research is descriptive qualitative. The data collection are using the method of observation, in-depth interview, and documents. The conclusion of this research is the political identity of muslim Javanese village to PKS done by affiliated become cadre, rooter, and PKS voter. The political support of muslim Javanese village, impact on strengthening PKS as a identity-based parties in Denpasar.   Keywords: political identity, muslim, Javanese village, PKS